Controversies regarding the new oral anticoagulants for stroke prevention in patients with atrial fibrillation. (June 2014) - Mohanty, Bibhu D; Looser, Patrick M; Gokanapudy, Lakshmi R; Handa, Rishi; Mohanty, Sudipta; Choi, Sharon S; Goldman, Martin E; Fuster, Valentin; Halperin, Jonathan L
Increasing use of the new oral anticoagulants (NOACs) – dabigatran, rivaroxaban, and apixaban – has prompted considerable discussion in the medical community even as warfarin remains the mainstay of therapy. This article raises 10 controversial issues regarding the use of NOACs for stroke prevention in patients with atrial fibrillation, and offers a review of the latest available evidence. We provide a brief overview of the mechanism and dosing of these drugs, as well as a summary of the key clinical trials that have brought them into the spotlight. Comparative considerations relative to warfarin such as NOAC safety, efficacy, bleeding risk, reversibility, drug-transitioning and use in patients well controlled on warfarin are addressed. Use in select populations such as the elderly, those with coronary disease, renal impairment, or on multiple anti-platelet drugs is also discussed. Finally, we consider such specific issues as comparative efficacy, off-label use, cost, rebound and management during events. Ultimately, the rise of the NOACs to mainstream use will depend on further data and clinical experience amongst the medical community.